Efektivitas Media Game SnakeMind Terhadap Kemampuan Berpikir Analitis Peserta Didik Kelas X pada Pembelajaran Akidah Akhlak di MAN 2 Tuban - Maimunah, Karismatul; Wildan Ittaqillah, Ahmad; Asroful Anam, Muhammad; Fauzi, M. (QAYID : Jurnal Pendidikan Islam, 2026)
This research is motivated by the low analytical thinking ability of students in learning Akidah Akhlak, which is seen from their difficulty in examining religious issues in depth. The purpose of this study is to determine the effect of using the SnakeMind Game media, a learning media based on an educational game of moving snakes designed to train students to understand questions, analyze alternative answers, and make appropriate decisions during the learning process. The research was conducted at MAN 2 Tuban using a pre-experimental approach through a one group pretest–posttest design. The research subjects consisted of 28 students of class X-1. Data were collected through analytical thinking ability tests given before and after the application of the media, then analyzed using a paired sample t-test and N-Gain calculation. The results of the analysis showed a significant increase in ability. The average pretest score of 64.04 increased to 82.39 in the posttest. The significance value (2-tailed) of 0.000 (<0.05) indicates a significant difference between before and after treatment. Furthermore, the N-Gain value ranged from 0.45 to 0.59, with an average of 0.5127, which falls into the moderate category. These findings indicate that the SnakeMind Game is quite effective in improving students' analytical thinking skills in learning about Aqidah Akhlak. This study has limitations such as a limited sample size, the use of a single class without a control group, and the material focusing solely on Aqidah Akhlak. Therefore, further research is recommended to involve a wider sample, add a comparison group, and test the application of the SnakeMind Game on different materials and educational levels to obtain more comprehensive results.